Resources for Asian studies in selected libraries in the Greater Manila Area a survey - Encarnacion, Violeta V.; Vallejo, Rosa M.; Saniel, Josefa M. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1973)
This study is a survey of the five major Asian collections in the Greater Manila Area, namely, the Asian Center Library, the Ateneo de Manila University Library, the University of Santo Tomas Library, the Asian Library, and the National Library.
The Asian collections of these libraries are still in their infancy, the earliest one dating back to only sixteen years ago. Their development has been a response to the different interests, needs, emphases of universities as well as to the post-war moves of the Philippines towards forging closer links with the other Asian countries.
The materials in the five libraries' collections are varied. Consisting of both printed and non-printed forms, they represent four regions of Asia: East Asia; South Asia; Southeast Asia; and West Asia, as well as the fields of the social sciences, the humanities and the sciences. The materials are mainly in English and to a lesser extent, in the indigenous languages. The latter are generally in Chinese and Japanese. In terms of country and area, subject and language, the levels of literature representation in each of the five libraries, vary.
As far as the organization of materials is concerned, each library has adopted the method which best fits its circumstances. A uniform classification scheme for Asian materials and other materials in each library is evident. For convenience those written in the indigenous languages are usually separated from the English language materials.
In the development of the five libraries' Asian collections it appears that grants from philanthropic foundations have constituted the main sources of funds for the purchase of materials on Asia. Despite this support, however, the status of these collections is far from satisfactory. Much spadework has to be done even in keeping up with current acquisitions.
Thesis (M.L.S.)--University of the Philippines, Diliman
Typescript.
Vita.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Asia--Bibliography.; Libraries--Philippines.